The internationalization of the Argentine beekeeping sector from a business perspective with an emphasis on cooperatives - Andrieu, Jimena; Bernal Jurado, Enrique; v, Adoración (REVESCO. Revista de Estudios Cooperativos, 2024)
Among the countries of the global South, Argentina faces the challenge of developing through the internationalization of its economy, based on an export matrix of primary products of agricultural origin. This poses challenges for overcoming the limitations to development derived from exports based on processes of historical appropriation of the free gift of nature. For this reason, we analyze which business characteristics can contribute to a better export performance with equity criteria. The configurational approach fills a gap in the literature by assessing how various combinations of business attributes explain an entity's performance in foreign markets. The Qualitative Comparative Analysis (QCA) method is used to study the Argentinean beekeeping sector. A survey was carried out in the year 2022 to entities with legal personality taxed in beekeeping primary production in Argentina. Thus, a fuzzy set analysis is proposed in order to recover the characteristics of the firms that positively affect the higher degree of linkage with foreign markets by evaluating two models that differ from each other by observing whether the export is direct or mediated by third parties. The results show that the following factors have a positive influence on greater internationalization in the study area: the size of the entity, vertical integration strategies and access to financing. Regarding the legal form of cooperative, a positive occurrence is observed for the general model; however, in the direct exports model the occurrence is negative. Regarding the impact of market orientation, the general model shows a negative impact on export performance, but the second model shows a positive impact. Therefore, the evidence provides key elements for understanding the challenges of internationalization in the business framework of Argentinean beekeeping, which will surely be useful in the transfer of knowledge to the sector
Keywords: Social economy; configurational approach; natural honey; exports; agricultural sector; integration